Bioinspired intrinsic control of freeze cast composites: Harnessing hydrophobic hydration and clathrate hydrates. (1st August 2016) - Naleway, Steven E.; Yu, Christopher F.; Hsiong, Rachel L.; Sengupta, Arijit; Iovine, Peter M.; Hildebrand, John A.; Meyers, Marc A.; McKittrick, Joanna
Abstract: Bioinspired ZrO2 -epoxy, two-phase composite materials were fabricated by the freeze casting fabrication technique followed by polymer infiltration. These materials were intrinsically controlled by adding varying concentrations of the monofunctional alcohols ethanol (EtOH), n -propanol ( n -PrOH) and n -butanol ( n -BuOH). The microstructures of freeze cast scaffolds created with these alcohol additives demonstrated maximum pore areas (peak A p ) at concentrations of 10, 5–7 and 3 vol% for EtOH, n -PrOH and n -BuOH respectively. Differential scanning calorimetry analyses of binary mixtures of these additives and water suggested only n -PrOH was capable of developing clathrate hydrates. Measurements of the adiabatic compressibility of complete freeze casting slurries showed that a similar room temperature phenomenon, hydrophobic hydration, was occurring in all cases with the maximum effect occurring at the same additive concentrations as the peak A p values. This highlights that effects occurring within the slurry at room temperature and before freezing may have a significant effect on the freeze casting process. Analysis of the mechanical properties shows that infiltration of the scaffolds can provide resistance to Euler buckling, resulting in strengths of ∼3 orders of magnitude greater than uninfiltrated (and therefore unsupported) scaffolds. This suggests that layered structural design elements, found throughout nature, may be harnessing this Euler buckling resistance to increase strength. Graphical abstract: